Вплив умов синтезу на властивості наночастинок заліза, отриманих методом хімічного осадження - Нгуєн, Тієн Хіеп; Мінь, Нгуєн Ван; Хунг, Нгуєн Мань; Нгі, Хо Тхань (Physico-technological Institute of Metals and Alloys, 2023)
In this paper, the influence of synthesis conditions on the properties of iron nanoparticles obtained by chemical deposition method was studied. Fe nanoparticles were obtained by hydrogen reduction of their hydroxide compounds Fe(OH)2, FeOOH at 400 °C and by using the borohydride method (direct precipitation of iron nanoparticles from FeCl3 solution using NaBH4 solution as a precipitant). The Fe(OH)2 and FeOOH hydroxides were previously synthesized by chemical precipitation from the corresponding solutions of iron (II) sulfate FeSO4 and iron (III) chloride FeCl3 using a precipitant – alkali solution NaOH 10 %wt. at a pH of 9. To study samples of the obtained Fe nanoparticles, the methods of X-ray phase analysis (XRD), scaning electron microscopy (SEM), and measurements of the specific surface area via low-temperature nitrogen adsorption (BET) were used. The result of X-ray diffraction method shows that all obtained nanopowder samples contain a pure Fe metal phase with a (bcc) crystal structure. The results of SEM and BET methods revealed that among the obtained samples, Fe nanoparticles synthesized by the borohydride method have the highest fineness. In this work, the effect of various concentrations (0.1, 0.5 and 1 %) of the potato starch stabilizer on the characteristics of Fe nanoparticles obtained by the borohydride method was also studied. As a result of electron microscopic analysis of the samples, it was shown that at a low concentration (0.1 %) of the stabilizer – potato starch, the obtained Fe nanoparticles mostly have a finely needlelike form. With increasing concentration of the stabilizer, the particles tend to round their shape, stick together and form large spherical agglomerates. The characteristic sizes of Fe nanoparticles in the sample with a starch concentration of 0.1 % are of the order of 40 nm, with an increase in the stabilizer concentration up to 0.5 and 1 %, Fe nanoparticles grow strongly and reach a size of hundreds of nm. The result of measuring the specific surface area of the samples by the BET method is also in a good agreement with the result of measuring the average size of the nanoparticles using SEM data that the sample of iron nanoparticles obtained with the presence of potato starch 0.1 % has the most developed surface. Thus, the synthesis of iron nanopowder using the borohydride method in the presence of 0.1 % potato starch makes it possible to obtain qualitatively stable fine nanoparticles.